2018
DOI: 10.2175/106143017x15131012153103
|View full text |Cite
|
Sign up to set email alerts
|

Free Chlorine Disinfection of Full‐Scale MBR Effluent to Achieve 5‐Log Virus Inactivation

Abstract: A series of full-scale testing was performed at the City of Lathrop Consolidated Treatment Facility to determine the "concentration times time" (Ct) value for free chlorine disinfection of nitrified membrane bioreactor (MBR) effluent to achieve more than 5-log virus inactivation. The full-scale testing consisted of tracer study, chlorine decay study, and virus seeding study. The virus seeding study was performed at a flow rate of 1 million gal/d (3800 m3/min), which corresponded to a theoretical contact time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Chlorine disinfection is used to inactivate pathogens from the wastewater and to provide ongoing protection against regrowth of pathogens by maintaining a chlorine residual in the reclaimed water. In the presence of ammonium, free chlorine (uncombined chlorine in the form of HOCl or OCl − ) will rapidly form chloramines, which also act as disinfectants, but are much less effective than free chlorine ( Ikehata et al, 2018 ). At high ratios of chlorine to ammonium, chlorine is consumed at a ratio of 7.6 mg of chlorine per mg of ammonium ( Pressley et al, 1972 ), implying that even small variations of ammonium concentrations result in large variations of the chlorine demand.…”
Section: Resultsmentioning
confidence: 99%
“…Chlorine disinfection is used to inactivate pathogens from the wastewater and to provide ongoing protection against regrowth of pathogens by maintaining a chlorine residual in the reclaimed water. In the presence of ammonium, free chlorine (uncombined chlorine in the form of HOCl or OCl − ) will rapidly form chloramines, which also act as disinfectants, but are much less effective than free chlorine ( Ikehata et al, 2018 ). At high ratios of chlorine to ammonium, chlorine is consumed at a ratio of 7.6 mg of chlorine per mg of ammonium ( Pressley et al, 1972 ), implying that even small variations of ammonium concentrations result in large variations of the chlorine demand.…”
Section: Resultsmentioning
confidence: 99%
“…The tracer study, chlorine decay study, and virus seeding study have reported at full‐scale testing a nitrified MBR to achieve more than 5‐log virus inactivation (Ikehata, Li, Komor, & Gibson, 2018). The concentration–time (Ct) value for free chlorine disinfection in the effluent can be as small as 3 mg min/L to be sufficient to achieve 5‐log inactivation of MS2 bacteriophage.…”
Section: Designmentioning
confidence: 99%
“…Today, membrane bioreactors (MBRs) are increasingly used as a barrier in on-site water reuse systemsespecially in small-scale systems with fewer than 50 people equivalentand are considered a best available technology (Branch et al, 2016;Lesjean et al, 2011). Disinfection of the water is mostly achieved through chlorination, due to its broad-spectrum efficacy and low cost (Ikehata et al, 2018).…”
Section: Introductionmentioning
confidence: 99%